The technological and economic operating conditions of the Innofreight container transport system - Široký, Jaromír (Kaunas University of Technology, 2020)
This paper is focused on further application of the Innofreight container transportation system in the Czech Republic, Austria and Slovakia. The author describes both the technical and operating characteristics of the most widely used transportation systems in railway transport of bulk material. It also provides a comparative analysis of the Innofreight container transportation system usage in selected European countries and in the Czech Republic, Austria and Slovakia. The aim of this paper is to set criteria determining the technological and economic interfaces of such system, as well as to suggest the implementation of such system into a specific transportation chain.
Technologické a ekonomické aspekty provozu systému Innofreight
Keywords: container; innofreight; operating; bulk material; kontejner; innofreight; provoz; přeprava uhlí